2015
DOI: 10.1097/spc.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptides 1 and 2

Abstract: The intestinal GLPs have shown beneficial effects in experimental trials and have potential for therapeutic use. In type 2 diabetic and obese patients, GLP secretion is impaired. Elucidating the role of these endogenous hormones could lead to the identification of mucositis risk factors and an alternative preventive therapy for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…We speculate that future studies should determine the usefulness of one of these hormones as a biomarker for mucositis [67]. …”
Section: Discussionmentioning
confidence: 99%
“…We speculate that future studies should determine the usefulness of one of these hormones as a biomarker for mucositis [67]. …”
Section: Discussionmentioning
confidence: 99%
“…Mucositis is commonly believed to primarily impact the oral cavity, although it can also affect the entire GI tract [79][80][81]. GI toxicity may impair vital GI functions, resulting in microbial translocation with inflammatory and infectious consequences [79,[82][83][84][85][86]. Consequently, multiple studies have shown links between oral and intestinal toxicity generated by chemotherapy and unfavorable treatment outcomes, such as fever, severe infections, and overall death [78,82,87,88].…”
Section: Bc For Chemotherapy-induced Gi Toxicity In Acute Lymphoblast...mentioning
confidence: 99%
“…(6-13) Important insight has also been provided on weight loss as well as nutrition support options for patients in need of supportive and palliative care. (14) (15, 16) Investigators and clinicians have also shared their valuable knowledge on novel approaches to understanding therapy related intestinal toxicities including symptom clustering(17), physiologic approaches(18), pathophysiologic mechanisims(19-22), new measurement tools/approaches(23-27) and understanding of therapy specific toxicities. (28, 29)…”
mentioning
confidence: 99%